Using Bamboozle Games To Improve Students’ Vocabulary In Understanding Narrative Text - Wulandari, Wahyu; Dias Andris Susanto; Faiza Hawa (Lumbung Pare Cendekia, 2024)
This research aims to know the significance different of using Bamboozle games of the students' vocabulary ability in comprehending narrative texts. This study used a quantitative approach. This research used an experimental design consisting of two groups, namely the experimental group and the control group. The population in this study was class XI students of SMP N 1 Penawangan for the 2023/2024 academic year. The samples from this research were class XI H, totaling 30 students for the experiment group, and class XI E, totaling 30 students for the control group. This technique in the research was a quasi-experiment. The writer found that Bamboozle media has improved students' vocabulary abilities. Based on the research findings, there is significant improvement between the pre-test and the post-test. Based on data analysis, the pre-test result in the experiment group was 67,67 while the post-test was 83,07. In the control group, the pre-test result was 66.4, while the post-test result was 76.67. Apart from that, based on the paired sample test table, the result shows a sig (2-tailed) of 0.000 < 0.05. Therefore, it can be concluded that Bamboozle games can improve students’ vocabulary in understanding narrative text.